Thermal bioclimatic condition of different urban parks - Nordin, Syaza Syahirah (2019)
Urban park provides many facilities and benefits that can be beneficial to urban citizens. Human thermal comfort in every urban park is important in order to make sure the user is thermally satisfied while using the urban park. However, different urban parks give different thermal satisfaction level because the tree compositions and arrangement at each of the urban park are different. Therefore, the objectives of this study were to investigate the influence of different types of park on human thermal comfort condition and to determine the relationships between human thermal comfort with tree characteristics. Three parks in Putrajaya were chosen as study area because of their distinct characteristics where Taman Saujana Hijau is a recreation vegetation type area, Taman Warisan Pertanian is an agriculture vegetation type area and Taman Rimba Alam is forest vegetation type area. Microclimate condition parameters of air temperature, relative humidity, wind speed, solar radiation and mean radiant temperature were measured and then used in Physiological Equivalent Temperature (PET) Index to estimate the human thermal comfort conditions. Tree characteristics such as height, canopy cover and canopy spread were also measured. This study found that different types of urban park significantly affected the human thermal comfort where PET was reduced up to 7°C (from strong heat stress to moderate heat stress) between Taman Rimba Alam with the other two parks. This is due to Taman Rimba Alam has more canopy coverage compared to Taman Saujana Hijau and Taman Warisan Pertanian. Moreover, there were significant relationship analyses between human thermal comfort and tree characteristics such as canopy cover, tree height and canopy spread. This shows that the tree characteristics and canopy coverage in park greatly influence the human thermal comfort. This study can help in the management and planning of urban park to improve the park thermal comfort conditions through consideration of the vegetation compositions and thermal conditions in an urban park.